Two species of Nemertopsis (Nemertea: Hoplonemertea: Monostilifera) living in association with Capitulum mitella (Crustacea: Cirripedia: Thoracica: Lepadomorpha) - Kajihara, Hiroshi (Zootaxa, 2007)
Two species of the monostiliferous hoplonemerteans, Nemertopsis quadripunctata (Quoy & Gaimard, 1833) and Nemertopsis mitellicola sp. nov., are reported from Shirahama, Wakayama, Japan, based on material obtained among the gooseneck barnacle, Capitulum mitella (Linnaeus, 1767). Redescription of Nemertopsis quadripunctata provides some anatomical features not reported in previous literature; these include: the rhynchodaeum opening to the dorsal portion of the oesophagus in front of the brain, and the oesophagus leading farther anteriorly to open subterminally to the exterior as a mouth; mid-dorsal vessel entering the rhynchocoel to form a single vascular plug; and the epidermis possessing a small pit in cross section, the pit being antero-posteriorly continuous, forming a complete sagittal furrow in the post-cerebral region of the body for at least 1 cm in length. Nemertopsis mitellicola sp. nov differs from all the congeners in having a spirally sculptured central stylet, lateral diverticula on the intestinal caecum, and a cephalic patch, from which two longitudinal dorsal stripes extend backward.